A PARADOX IN THE EU MIGRATION MANAGEMENT - (:unkn) unknown (FRIEDRICH EBERT STIFTUNG E V, 2009)
Since the end of the Cold Wal; due to securitization, migration has been perceived as a source of insecurity by the European societies. This has resulted by the introduction of restrictive migration policies in the Member States of the European Union (EU). Similar to the national migration policies, the ones that resulted in the EU level are also believed to he restrictive. According to many academics; EU migration policies owe their restrictive nature also to the securitization of migration in the EU. Paradoxically, according to the projections of the next decades, the European economy is in need of migrants for renovation. Following these lines the argument of this study is: 'Despite the fact that the EU needs migrants, securitization of migration has been taking place in the EU, which denotes a paradox in its migration management'.
Keywords: societal security; securitization; migration; European Union; SECURITIZATION; UNION